INTERNALISASI KONSEP USHULIYUN DAN MUHADDISUN TERHADAP IMPLEMENTASI SUNNAH DALAM PROSES ISTIMBATH HUKUM - Nenan Julir (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2015)
Internalization concept of Ushuliyun and Muhaddisun on implementation of sunnah inthe process of concluding the law. One of the main source of law in Islam is Al-qur’an, but inunderstanding qur’an and implementing the qur’an in the life need Al-Sunnah, which the secondsource of Islamic law. Qur’an and Al-Sunnah should be both covering Islamic teaching. The writer inthis paper aimed at analyzing al-sunnah in two ways: Muhaddisun and Ushuliyun. The writer is tryingto understand the concept of Muhaddisun and Ushuliyun in understanding al-sunnah as the secondsource of Islami law and how is their process in concluding the islamic law. The result shows that inunderstand al-sunnah, the Muhaddisun differentiate the hadith according to their sanad, matan andrawi. And thus, the selected hadith will be used for argumentation in concluding the law. While theUshuliyun in concluding the law they combined hadith and other argumentations, taking in to accountthe source of hadith, and deeply understanding the connotation meaning of hadith